Pengembangan Modul Pteridophyta di Taman Purbakala Pugung Raharjo sebagai Sumber Belajar di Masa Pandemi Covid-19 SMA Muhammadiyah 1 Sekampung Udik: (Development Of The Pteridophyta Module In The Pugung Raharjo Archaeological Park as a Learning Resource During The Covid-19 Pandemic SMA Muhammadiyah 1 Sekampung Udik) - Tri Andri Setiawan; Ahmad Fadilah; Yudiyanto Yudiyanto; Suhendi Suhendi (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2022)
The purpose of this study was to develop, analyze the feasibility and analyze the responses of teachers and students to the developed product. This study uses the ADDIE development model. The test subjects in this study were one teacher and ten students of class X MIA SMA Muhammadiyah 1 Sekampung Udik. The data analysis technique in this research is quantitative and qualitative data analysis. The results of product validation by material experts were carried out three times, obtained a percentage score of 94% (Very valid), while the results of module expert validation were carried out twice, obtained a percentage score of 94% (Very valid). The results of the teacher's response obtained a percentage score of 80% (Very valid) and the results of student responses obtained a percentage score of 71.25% (Valid). Based on the results of the feasibility assessment, the average percentage score was 84.8%, so it can be concluded that the Pteridophyta module product developed is very suitable for use in Biology learning. Key words: Learning resources, Module, Pteridophyta Abstrak Tujuan penelitian ini adalah mengembangkan, menganalisis kelayakan dan menganalisis respon guru dan siswa terhadap produk yang dikembangkan. Penelitian ini menggunakan model pengembangan ADDIE. Subjek ujicoba pada penelitian ini yaitu satu orang guru dan sepuluh orang siswa kelas X MIA SMA Muhammadiyah 1 Sekampung Udik. Teknik analisis data dalam penelitian ini adalah analisis data kuantitatif dan kualitatif. Hasil validasi produk oleh ahli materi dilakukan sebanyak tiga kali, diperoleh persentase skor 94% (Sangat valid), sedangkan hasil validasi ahli modul dilakukan sebanyak dua kali, diperoleh persentase skor 94% (Sangat valid). Hasil respon guru diperoleh persentase skor 80% (Sangat valid) dan hasil respon siswa diperoleh persentase skor 71,25% (Valid). Berdasarkan hasil penilaian kelayakan diperoleh persentase rata-rata skor sebesar 84,8%, sehingga dapat disimpulkan bahwa produk modul Pteridophyta yang dikembangkan sangat layak digunakan dalam pembelajaran Biologi. Kata kunci: Modul, Pteridophyta, Sumber belajar